Finite Difference Methods For Linear Fuzzy Time Fractional Diffusion And Advection-Diffusion Equation - Zureigat, Hamzeh Husni Rasheed (2019)
Fractional differential equations have attracted considerable attention in the last decade or so. This is evident from the number of publications on such equations in various scientific and engineering fields. Crisp quantities in fractional differential equations which are deemed imprecise and uncertain can be replaced by fuzzy quantities to reflect imprecision and uncertainty. The fractional partial differential equation can then be expressed by fuzzy fractional partial differential equations which can give a better description for certain phenomena involving uncertainties. The analytical solution of fuzzy fractional partial differential equations is often not possible. Therefore, there is great interest in obtaining solutions via numerical methods. The finite difference method is one of the more frequently used numerical methods for solving the fractional partial differential equations due to their simplicity and universal applicability. In this thesis, the focus is the development, analysis and application of finite difference schemes of second order of accuracy and compact finite difference methods of fourth order of accuracy to solve fuzzy time fractional diffusion equation and fuzzy time fractional advection-diffusion equation. Two different fuzzy computational techniques (single and double parametric form of fuzzy number) are investigated. The Caputo formula is used to approximate the fuzzy time fractional derivative. The consistency, stability, and convergence of the finite difference methods are investigated. Numerical experiments are carried out and the results indicate the effectiveness and feasibility of the schemes that have been developed.